2019
DOI: 10.3390/su11041087
|View full text |Cite
|
Sign up to set email alerts
|

Public-Private Partnerships for Sustainable Development: Exploring Their Design and Its Impact on Effectiveness

Abstract: Public-private partnerships for sustainable development have been in operation for several decades from the local to the international level [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 11 publications
1
21
0
1
Order By: Relevance
“…This finding corresponds with conclusions that have been drawn in other PPP studies [97,135]. In essence, profit is a fundamental goal in an enterprise's willingness to participate in PPPs [93]. One explanation for the lower factor loading value than risk index for Component 3 could be that profit is not only comprised of economic but also public considerations [25].…”
Section: External Environmental Risk Factorssupporting
confidence: 87%
See 1 more Smart Citation
“…This finding corresponds with conclusions that have been drawn in other PPP studies [97,135]. In essence, profit is a fundamental goal in an enterprise's willingness to participate in PPPs [93]. One explanation for the lower factor loading value than risk index for Component 3 could be that profit is not only comprised of economic but also public considerations [25].…”
Section: External Environmental Risk Factorssupporting
confidence: 87%
“…Therefore, the PPP model is well-suited to SLCT construction due to its ability to satisfy multiple partners' interests and demands [18,73,90] by way of funds, talent, operational experience, and financial insurance [91]. Private partners are the key stakeholders in SLCT PPP projects [17,92,93], and their willingness to participate can directly contribute to sustainable urbanization. Related studies have explored the selection criteria for private partners from the perspectives of governments [94,95] and the willingness of private sectors to invest in the infrastructures PPP projects from case studies in the UK [25,96,97] and emerging markets [23,94].…”
Section: Ppp Modelmentioning
confidence: 99%
“…In fact, the 2030 Agenda for Sustainable Development calls explicitly for action to "all countries and all stakeholders, acting in collaborative partnership, to implement the plan" [27]. In this context, the effectiveness of these PPPs will be crucial to achieving the SDGs [100], regarding its ability to create sustainable futures in terms of economic, social, and environmental considerations. Yet, prior studies have shown that PPPs also offer a series of disadvantages or limitations, such as high transaction costs, limited innovation, or difficulties integrating service models in the case of multiple stakeholders with conflicting interests [12,101].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The emergence of public-private partnerships combines public and private policy instruments and all components of the policy-process in more collaborative form of governance (Lambin & Thorlakson, 2018). The actors in PPPs develop relations and influence the projects to make specific attention towards sustainability concerns in the implementation (Marx, 2019). Legitimacy is not only about direct decision-making influence, but also assure the decisions have been made in a fair and unbiased manner through transparency and representation of relevant social and interest groups (Tyler & Lind, 1992).…”
Section: Environmental Management and Sustainable Developmentmentioning
confidence: 99%
“…All members of successful partnerships are working toward the same end and dedicated to achieve common goals. Private actors in public-private partnerships are involved in policy-making including agenda-setting, negotiation, resource provision implementation, monitoring, and enforcement (Marx, 2019). The proliferation of publicprivate partnerships is rapidly reconfiguring the international forestry landscape.…”
Section: Introductionmentioning
confidence: 99%